2007
DOI: 10.3141/2031-05
|View full text |Cite
|
Sign up to set email alerts
|

Bicycle Level of Service for Arterials

Abstract: This paper documents a study sponsored by the Florida Department of Transportation (FDOT) to create a model that predicts how bicyclists perceive the arterial roadway environment. It builds on the highly successful adopted segment and intersection bicycling level of service (LOS) models. Data for the new bicycle LOS for arterials model were obtained from FDOT's innovative Ride for Science field data collection event and video simulations. The data consisted of participants' perceptions of how well roadways met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(28 citation statements)
references
References 4 publications
0
28
0
Order By: Relevance
“…Researchers and practitioners have developed a number of quality-of-service (QOS) models for bicyclists (8)(9)(10)(11)(12)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28). The six most relevant methods are summarized in Table 1.…”
Section: Prior Researchmentioning
confidence: 99%
“…Researchers and practitioners have developed a number of quality-of-service (QOS) models for bicyclists (8)(9)(10)(11)(12)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28). The six most relevant methods are summarized in Table 1.…”
Section: Prior Researchmentioning
confidence: 99%
“…In their random-sample survey of Portland, Oregon, residents, Dill and Voros found that nearly 40% of people who wanted to bicycle more cited a lack of bike lanes or trails as a barrier to doing so (11). Research by Petritsch and Landis on bicycle LOS in Florida found that the presence or absence of a bicycle lane was the most commonly cited reason for giving a roadway a high or low score, respectively (12). In their analysis of perceived cycling risk and route acceptability, Parkin et al found that bicycle lanes could mitigate the perceived risk of bicycling near high amounts of auto traffic (13).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Supplementary methods to the initial list were found through snowballing of references and searches in the Scopus database. The criterion results in the exclusion of such methods as those that are focused solely on intersections [18], separated bicycle or shared paths [19][20][21], rural areas [22,23], urban arterials [24], or bicycle lanes [25,26]. Audit-based metrics are also excluded from Table 1, including those in Australia and the UK that use the term "Cycling Level of Service" [9,27,28] and select others that use the term bicycle level of service but are either 'scorecard' based or lack an empirical foundation for the combination of variables [29,30].…”
Section: Introductionmentioning
confidence: 99%